Sağlık inanç modeline dayalı çözüm odaklı yaklaşımın sigara bırakma polikliniğine başvuran bireylerin sigara bırakma süreçlerine etkisi - Kıroğlu,Birsen (My University, 2025)
Sağlık inanç modeline dayalı çözüm odaklı yaklaşımın sigara bırakma polikliniğine başvuran bireylerin sigara bırakma süreçlerine etkisi Amaç: Bu çalışma sigara bırakma polikliniğine başvuran bireylere uygulanan Sağlık İnanç Modeline Dayalı Çözüm Odaklı Yaklaşımın sigara bırakma süreçlerine etkisini değerlendirmek amacıyla yapıldı. Gereç ve Yöntem: Randomize kontrollü tasarım olarak yürütülen ve araştırmanın evreni İstanbul’daki bir hastanenin sigara bırakma polikliniğine başvuran bireyler (N:194) olan araştırma Eylül 2024-Kasım 2024 tarihlerinde yürütüldü. Araştırmanın örneklem sayısı yapılan power analiz sonucunda 176 olarak belirlendi. Bireyler deney (n: 88) ve kontrol (n: 88) gruplarına randomizasyon ile atandı. Literatür ve uzman görüşleri doğrultusunda oluşturulan oturumlar haftada bir gün toplamda 4 oturum olarak uygulandı. Veriler, Sağlık İnanç Temelli Sigara Bırakma Süreci Ölçekleri (SİTSBSÖ) ile oturum öncesinde, oturum sonunda ve oturumdan 1 ay sonra toplandı. Bulgular: Girişim öncesi deney ve kontrol grubundaki bireylerin sosyodemografik özellikleri ve ölçek puanlarında benzerlik saptandı (p>0.05). Girişim sonrası (p<0.05) deney grubunun kontrol grubuna göre sigara bırakma süreçleri puan ortalamaları anlamlı düzeyde olumlu yönde değişti. İzlem testte (p<0.05) deney grubunun kontrol grubuna göre ciddiyet algısı ve normatif inanç ölçek puan ortalamaları daha yüksek bulundu. Kontrol grubunun ön test-izlem test bilgi, ciddiyet algısı, engel algısı, teşvik ediciler, öz-etkililik, genel sağlık motivasyonu ve normatif inanç puan ortalamalarında anlamlı fark bulunmadı (p<0.05). Sonuç: Hemşire liderli uygulanan model temelli yapılandırılmış çözüm odaklı yaklaşım girişiminin sigara içen bireylerin sigara bırakma süreçlerinde etkili olduğu görüldü. Yapılandırılmış bu girişimin sigara bırakma polikliniklerinde yürütülen rutin tedavi programlarında hatırlatıcı oturumlar eklenerek kullanılması önerilmektedir.

The effect of solution-focused approach based on health belief model on smoking cessation processes of ınviduals applying to smoking cessation polyclinic Objective: This study was carried out to evaluate the effect of the Solution-Focused Aprroach Based on Health Belief Model applied to individuals applying to the smoking cessation clinic on their smoking process. Materials and Methods: The research, which was carried out as a randomized controlled design, was conducted with individuals (N: 194) who applied to the smoking cessation clinic of a hospital in İstanbul between September 2024 and November 2024. The sample number of the study was determined as 176 as a result of the power analysis. Individuals were assigned to experimental (n:88) and control (n:88) groups by randomization. The sessions, which was created in line with the literature and expert opinions, was applied once a week as a total of 4 sessions. Data were collected before, at the end of the sessions and 1 month after the sessions with the Health Belief Model Based Smoking Cessation Process Scales. Results: It was determined sociodemographic characteristics and scale scores of the individuals in the experimental and control groups were similar before the intervention (p>0.05). After the intervention (p<0.05), the mean scores of the smoking cessation processes of the experimental group changed significantly in a positive direction compared to the control group. In the follow-up test (p<0.05), the mean scores of the perception of seriousness and normative belief scale scores of the experimental group were higher than the control group. No significant difference was found in the mean scores of knowledge, perception of seriousness, perception of barriers, incentives, self-efficacy, general health motivation and normative beliefs of the control group in the pretest-follow-up test (p<0.05). Conclusion: The nurse-led model-based structured solution-oriented approach intervention was found to be effective in the smoking cessation processes of smokers. It is suggested that structured intervention should be by adding reminder sessions in routine treatment programs conducted in smoking cessation polyclinics.
The effect of solution-focused approach based on health belief model on smoking cessation processes of ınviduals applying to smoking cessation polyclinic
Keywords: Çözüm odaklı yaklaşım; Halk sağlığı hemşireliği; Halk sağlığı uygulaması; hemşirelik; nursing; Public health nursing; Public health practice; sağlık inanç modeli; sigara Health belief model; Sigarayı bırakma; smoking; Smoking cessation; soluted-focused approach; Turkey; Türkiye